2020
DOI: 10.1002/ps.6210
|View full text |Cite
|
Sign up to set email alerts
|

Host deprivation effects on population performance and paralysis rates of Habrobracon hebetor (hymenoptera: Braconidae)

Abstract: BACKGROUND Habrobracon hebetor (Hymenoptera: Braconidae) is a gregarious ectoparasitoid that attacks the larvae of several species of pyralid and noctuid moths. The reproduction and population dynamics of parasitoids in general are affected by host deprivation. However, how host deprivation affects H. hebetor is unknown. The effect of host deprivation on the parental generation, life table parameters, and the paralysis rate of the F1 generation of H. hebetor were evaluated using the age‐stage, two‐sex life tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(91 reference statements)
0
8
1
Order By: Relevance
“…The variances and standard errors of population parameters were estimated using a bootstrap method with 100,000 resamplings [ 31 ]. Differences between Ca-treated leaves and control leaves were calculated by using the paired bootstrap test based on the 5% significance level [ 32 , 33 ]. All of these analyses were performed by TWOSEX-MSChart [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The variances and standard errors of population parameters were estimated using a bootstrap method with 100,000 resamplings [ 31 ]. Differences between Ca-treated leaves and control leaves were calculated by using the paired bootstrap test based on the 5% significance level [ 32 , 33 ]. All of these analyses were performed by TWOSEX-MSChart [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…The larval ectoparasitoid Habrobracon hebetor (Say) (Hymenoptera: Braconidae) stands out as a potential biocontrol agent for stored pests [12]. This species has been promising in laboratory experiments to control various pest moths present in different stored product environments [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Chi and Yang (2003) examined the age‐stage, two‐sex life table for the ladybird predator, Propylaea japonica (Col.: Coccinellidae), and indicated that it could accurately describe the variability of predation rate with age and stage. This method was used in many studies based on predators and parasitoids (Ding et al, 2020; Farhadi et al, 2011; Ou et al, 2021; Ramos Aguila et al, 2021; Wang et al, 2022). Chi and Yang (2003) noted that in order to accurately reflect the variability of predation rate with stage and age, the daily consumption rates across the lifelong of a predator population should be assessed by the age‐stage structure of the life table.…”
Section: Introductionmentioning
confidence: 99%